PWE-081 Thioguanine Remains an Acceptable Alternative Immunosuppressant in IBD. (4th June 2013) - Patel, K V; Goel, R M; Kariyawasam, V C; Blaker, P A; Ward, M G; Mashari, S; Clark, A; Sastrillo, M; Duncan, J; Anderson, S H; Irving, P M; Sanderson, J D
Abstract : Introduction: A significant proportion of inflammatory bowel disease (IBD) patients do not tolerate conventional thiopurines (azathioprine (AZA) and mercaptopurine (MP)). Thioguanine (TG) remains an alternative immunomodulator (IM) and has been in regular use in the IBD clinic at Guy's & St. Thomas' for more than 10 years. Concerns remain regarding nodular regenerative hyperplasia (NRH) in long-term use. Methods: We aimed to describe the indications, efficacy, monitoring and sequelae of TG use in IBD patients. Patients prescribed TG for IBD from 2008–2012, subsequent to a previously published series, were reviewed. Results: 37 patients were identified (15 male, mean age 43 years). 29 patients had Crohn's disease with 2 having co-existing orofacial granulomatosis, 6 had ulcerative colitis and 1 had IBD-unclassified. All had previous exposure to AZA and/or MP. The indications for TG were thiopurine intolerance in 23 and thiopurine induced pancreatitis in 13 patients. Median duration of exposure was 11 months (IQR: 3–30). Maintenance doses were 20mg or 40mg. 20 patients (54%) were in clinical remission at the end of follow-up period, and 16 (41%) of these were steroid free. Mean TGN levels were 1177 pmol/8 × 10 8 RBC (range 70–3182 pmol/8x10 8 ). Differences in TGN concentrations in clinical responders and non-responders were not statistically significant. Treatment was withdrawn in 7 patients. Withdrawal was for adverse events in 3 patients, which resolved on TG withdrawal (neutropenic sepsis, pancytopenia and AST rise) and treatment failure in further 3 patients. TG was ceased in another after the diagnosis of metastatic breast cancer whilst receiving Adalimumab and concomitant TG for 12 months. 7 patients discontinued TG because of side effects occurring within 2 months of initiation. 11 patients had long-term exposure (> 18 months). Screening with liver biopsy and/or MRI-Liver was performed in 9 patients. All patients were screened with regular platelet counts and liver profile. None were diagnosed with NRH during follow-up. Conclusion: TG is a viable second-line IM and appears to be effective with an acceptable safety profile. Side effects are uncommon, occur early and cease upon TG withdrawal. Chief indications are previous failure of immunosuppressant therapy or thiopurine-associated pancreatitis. There were no cases of TG-associated pancreatitis. Concerns regarding hepatotoxicity and NRH were not manifest in this small series of patients in concordance with results from similar recent European series. Dedicated liver MRI screening along with quarterly liver profile and platelet counts to monitor for NRH should be offered to patients on long term therapy. Disclosure of Interest: None Declared.